Try another version of this question
Find the inverse of the following function:
`f^(-1)( x ) =`
To find the inverse of the function `f(x) = 12 x + 5`, start by expressing the function as `y== 12 x + 5`. Then, think about how you might rearrange this equation to solve for `x` in terms of `y`, remembering that the roles of `x` and `y` are switched in the inverse function.
Box 1: Enter your answer as an expression. Example: 3x^2+1, x/5, (a+b)/c
Be sure your variables match those in the question
`(`